DNA calorimetric force spectroscopy at single base pair resolution - P. Rissone; M. Rico-Pasto; S. B. Smith; F. Ritort (Nature Communications)
Abstract DNA hybridization is a fundamental molecular reaction with wide-ranging applications in biotechnology. The knowledge of the temperature dependence of the thermodynamic parameters of duplex formation is crucial for quantitative predictions throughout the DNA stability range. It is commonly assumed that enthalpies and entropies are temperature independent, and heat capacity changes ΔC p equal zero. However, it has been known that this assumption is a poor approximation for a long time. Here, we combine single-DNA mechanical unzipping experiments using a temperature jump optical trap with a tailored statistical analysis to derive the ten heat-capacity change parameters of the nearest-neighbor model. Calorimetric force spectroscopy establishes a groundbreaking approach to studying nucleic acids that can be further extended to chemically modified DNA, RNA, and DNA/RNA hybrid structures.